Energy in the German-Polish relationship: Acknowledging controversies - pursuing shared interests - Kai-Olaf Lang; Karsten Neuhoff; Ellen Scholl; Kirsten Westphal; Aleksandra Gawlikowska-Fyk (Stiftung Wissenschaft und Politik (SWP), 2017)
Germany and Poland stand as examples of the differing interests of individual European Union (EU) member states in energy policy. However, both countries are crucial for filling an Energy Union with substance. Yet, progress in bilateral engagement has stalled, as controversies, for example over Nord Stream II, threaten to distract attention from other issues and avenues for energy cooperation. While acknowledging disagreements, the focus should be on identifying areas of agreement and opportunities for cooperation. Although the difficulty of resolving highly controversial issues is not to be discounted, addressing them will require taking steps to establish trust while designing programs and projects to transform the idea of solidarity from rhetoric into reality. (SWP Comments)
Keywords: 320